Effects of exercise supplementary to standard therapy on cognition and sleep in depression: a randomised controlled trial - Liu, Cong; Zhai, Fei; Li, Min; Wang, Huiying; Zhang, Jianhong; Ji, Ziyang; Li, Hengfen (Frontiers in Psychiatry, 2026)
PurposeTo explore the Effects of Exercise Supplementary to Standard Therapy on Cognition and Sleep in Depression.MethodsWe randomized 273 inpatients with first-episode severe depression, 234 completed 6 weeks, conventional treatment, conventional treatment combined with aerobic exercises and conventional treatment combined with stretching or resistance training exercises group. Hamilton Depression Scale-24 (HAMD24), Pittsburgh Sleep Quality Index (PSQI), Montreal Cognitive Assessment (MOCA), Chinese Version of the Trail-Making Test (C-TMT), and Stroop Color and Word Test (SCWT) were used to evaluate the patients respectively before and after intervention. The primary analysis estimated was the between-group difference in post-treatment scores at 6 weeks under randomized allocation (post-status estimated); within-group changes were summarized descriptively.ResultsAfter intervention, HAMD24, PSQI, C-TMT-A, and C-TMT-B scores of patients in each group were all lower than those before intervention. HAMD24, PSQI, and C-TMT-A scores of patients in Groups B and C showed lower than those of Group A. C-TMT-B score of patients in Group B was lower than that of Group C, and the score of Group C was lower than that of Group A. MOCA, SCWT scores of patients in each group were higher than those before intervention. Stroop Word and Stroop Color scores were significantly higher in Groups B and C than in Group A. MOCA and Stroop Color-Word scores of patients in Group B were higher than those of Group C. However, scores of Group C were higher than those of Group A.ConclusionBoth aerobic exercises and stretching or resistance training exercises as adjuncts to conventional treatment improved depressive symptoms, sleep quality, and cognitive function in patients with first-episode severe depression. Patterns were consistent with greater improvement in select executive-function measures in the aerobic arm; confirmation with baseline-adjusted analyses is warranted.